Paisaje: Imagen, entorno, ensamble - Andermann, Jens (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2008)
Despite explicitly recognizing its mediating function between culture and nature, both aesthetics and social science tend to reduce landscape, either to a mere construct of the gaze that beholds it or to the material result of human intervention into its thereby "culturized" natural environment. This essay argues that we should return to conceive of landscape as the process that runs from the image to the environment and vice versa, as an assemblage of the human and the non-human. In this way, it aims to sketch out a theoretical frame in which to historicize the landscapes of Latin American modernity.